2021
DOI: 10.1038/s41467-021-22634-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of von Willebrand factor via mechanical unfolding of its discontinuous autoinhibitory module

Abstract: Von Willebrand factor (VWF) activates in response to shear flow to initiate hemostasis, while aberrant activation could lead to thrombosis. Above a critical shear force, the A1 domain of VWF becomes activated and captures platelets via the GPIb-IX complex. Here we show that the shear-responsive element controlling VWF activation resides in the discontinuous autoinhibitory module (AIM) flanking A1. Application of tensile force in a single-molecule setting induces cooperative unfolding of the AIM to expose A1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 88 publications
3
87
0
Order By: Relevance
“…Moreover, caplacizumab, a bivalent nanobody targeting VWF, was approved by the FDA in 2019 for treating acquired TTP (aTTP) ( 44 , 45 ), a TTP deficiency due to the presence of inhibitory autoantibodies. A recent study indicated that caplacizumab binds the A1 domain (i.e., the platelet-binding domain) of VWF and allosterically inhibits the A1-platelet GPIbα receptor interaction under low and moderate shear, thereby exerting its antithrombotic function ( 46 ).…”
Section: Hemostatic Role Of Vwf/adamts13 Axismentioning
confidence: 99%
“…Moreover, caplacizumab, a bivalent nanobody targeting VWF, was approved by the FDA in 2019 for treating acquired TTP (aTTP) ( 44 , 45 ), a TTP deficiency due to the presence of inhibitory autoantibodies. A recent study indicated that caplacizumab binds the A1 domain (i.e., the platelet-binding domain) of VWF and allosterically inhibits the A1-platelet GPIbα receptor interaction under low and moderate shear, thereby exerting its antithrombotic function ( 46 ).…”
Section: Hemostatic Role Of Vwf/adamts13 Axismentioning
confidence: 99%
“…Here, we have investigated the effects of these linkers on A1 thermodynamics and function in binding to its ligand, GPIbα. Previous studies have examined the effect of the N-terminal linker or both linkers on various types of quantitative or nonquantitative binding assays and thermodynamics and found inhibitory effects on GPIbα binding from adding the N-linker or both linkers to A1 (Arce et al, 2021;Auton et al, 2012;Deng et al, 2018;Deng et al, 2017;Interlandi et al, 2017;Ju et al, 2013;Miyata & Ruggeri, 1999;Nakayama et al, 2002;Tischer et al, 2017;Tischer et al, 2014). We found that both the N and C-linker decreased A1 affinity for GPIbα and that for both the N and C-linker, O-glycosylated linkers decreased affinity more than polypeptide linkers.…”
Section: Discussionmentioning
confidence: 66%
“…It was also proposed that the N-and C-linkers interact with each other and form an autoinhibitory module that masks A1 (Deng et al, 2017). A force-dependent signature for breakage of this module has been reported that correlates with the combined expected extension of the N and C-linkers (Arce et al, 2021). An alternative mechanism has also been proposed by which the N-linker could regulate A1 affinity, i.e., by regulating the relative stability of the A1 native and intermediate states.…”
Section: Introductionmentioning
confidence: 99%
“…As seen previously for GPIbα and VWF fragments, the binding sensorgrams (Figure 2B,C) indicate this interaction proceeds with a very fast dissociation rate. 23 The kinetic fitting of such an interaction is difficult. Nevertheless, steady-state analysis of this interaction is in good agreement with ELISA results (Figure 2D).…”
Section: Asialo-aim-a1 Has Increased Binding Activitymentioning
confidence: 99%